Quantitative Descriptive Sensory Analysis of the Performance of Pregelatinised Starch-Protein Admixtures as Fat Mimetic in Wheat Bread - Ofosu, Isaac W.; Adjei, Isaac A.; Bah, Franklin B. Apea; Kwetey, Paula N.; Ankar-Brewoo, Gloria M.; Oduro, Ibok; Ellis, William O. (Pakistan Journal of Nutrition, 2009)
Quantitative descriptive sensory analysis was used to evaluate the performance of pregelatinised protein-starch admixture as fat mimetics in bread. In this work, two regimes of total fat replacements consisting of 50% protein: 50% starch admixture on one hand and 70% protein: 30% starch admixture on the other were compared to another two regimes of partial fat replacements consisting of 50% fat in composite with the above admixtures with 100% full fat bread as control to give a total of five treatments. Sensory quality was assessed by 24 trained assessors made up of 12 men and 12 females using attributes such as bread taste, crumb moistness, crust softness, cell structure, crumb and crust colours and overall acceptability. Analysis of variance revealed all treatments to be significantly different (p